2017
DOI: 10.1186/s12931-017-0505-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the endothelium in asthma and chronic obstructive pulmonary disease (COPD)

Abstract: COPD and asthma are important chronic inflammatory disorders with a high associated morbidity. Much research has concentrated on the role of inflammatory cells, such as the neutrophil, in these diseases, but relatively little focus has been given to the endothelial tissue, through which inflammatory cells must transmigrate to reach the lung parenchyma and cause damage. There is evidence that there is an abnormal amount of endothelial tissue in COPD and asthma and that this tissue and its’ progenitor cells beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 140 publications
(176 reference statements)
3
79
0
5
Order By: Relevance
“…The difference in strength of associations between the sexes was unexpected. It is not known whether this sex difference would be found in older cohorts or those with established lung or cardiovascular disease: most previous reports on associations between endothelial function and respiratory diseases comprise relatively smaller samples of older men and women and, as far as we are aware, none have investigated sex differences . We can only speculate on the reasons for this effect modification by sex.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The difference in strength of associations between the sexes was unexpected. It is not known whether this sex difference would be found in older cohorts or those with established lung or cardiovascular disease: most previous reports on associations between endothelial function and respiratory diseases comprise relatively smaller samples of older men and women and, as far as we are aware, none have investigated sex differences . We can only speculate on the reasons for this effect modification by sex.…”
Section: Discussionmentioning
confidence: 81%
“…Non‐invasive measures of endothelial function predict the risk of future cardiovascular events . Impaired endothelial function has been reported in both COPD and asthma, and the extent of endothelial dysfunction is associated with the severity of airflow obstruction . Assessing the pulmonary endothelium is difficult, but it has been suggested that airway inflammation causes endothelial dysfunction in the pulmonary circulation, which leads to systemic endothelial dysfunction .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Також доведено, що порушення бронхіальної прохідності значно впливає на стан ендотелію у хворих на хронічне обструктивне за-хворювання легень (ХОЗЛ) [4][5][6]. Продовжується вивчатися роль біологічних факторів, гіпоксії, сис-темного запалення, оксидативного стресу в розви-тку ендотеліальної дисфункції окремо при ХОЗЛ та НАСГ [7][8][9][10].…”
Section: вступunclassified